ChemInform Abstract: Asymmetric Synthesis and Molecular Docking Study of Enantiomerically Pure Pyrrolidine Derivatives with Potential Antithrombin Activity. Issue 50 (10th December 2013) - Ayan, Seylan; Dogan, Oezdemir; Ivantcova, Polina M.; Datsuk, Nikita G.; Shulga, Dmitry A.; Chupakhin, Vladimir I.; Zabolotnev, Dmitry V.; Kudryavtsev, Konstantin V.
Abstract Both enantiomers of pyrrolidine (III) are readily prepared by a zinc‐catalyzed asymmetric 1, 3‐dipolar cycloaddition of tert‐butyl acrylate (II) with aldimine (I).